HUBUNGAN ANTARA KETERAMPILAN DENGAN KINERJA KADER POSYANDU Studi Observasional Analitik Kader Posyandu di Wilayah Puskesmas Bangetayu Semarang - Nabila Azizah; Purwito Soegeng Prasetijono (PT. Hasba Edukasi Mandiri, 2026)
Posyandu (Integrated Health Post) is a community-based health service whose success is determined by the role of its cadres. Cadre skills, both technical and non-technical, play a crucial role in supporting their performance in health services. This study aims to analyze the relationship between skills and the performance of Posyandu cadres in the Bangetayu Community Health Center (Puskesmas) area in Semarang City. This is an observational analytical study with a cross-sectional design. The sample consisted of 76 Posyandu cadres selected using simple random sampling. Data were collected through observation and a structured questionnaire to assess cadre skills and performance. Data were analyzed univariately and bivariately using the Spearman correlation test. The results showed that the majority of cadres had sufficient skill levels (47.4%) and poor performance (39.5%). The Spearman correlation test showed a significant relationship between skills and Posyandu cadre performance (p < 0.001), with a correlation coefficient of 0.404, indicating a positive relationship of moderate strength. From these results, it can be concluded that there is a significant relationship between skills and the performance of Posyandu cadres in the Bangetayu Health Center work area, Semarang City.